Supersymmetric mixed boundary conditions in AdS2 and DCFT1 marginal deformations - Correa, Diego Hernán (2020)
We consider different supersymmetric mixed boundary conditions for scalar and fermionic fields in AdS2, searching for the dual description of a family of interpolating Wilson Loops in ABJM theory. The family, which interpolates between the bosonic 1/6 BPS loop and the 1/2 BPS loop, can be thought of as an exact marginal deformation in a defect CFT1. Confronting this property against holographic correlators and vacuum energy corrections singles out a particular boundary condition which we propose as dual to the interpolating family of Wilson loops.